2020
DOI: 10.1002/asia.202000717
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering Ability of a Synthetic Chelating Agent towards Copper(II) and Iron(III): A Detailed Theoretical and Experimental Analysis

Abstract: In the continuous effort to identify selective chelators towards bioavailable and toxic metal ions, the potential selectivity of a novel N,O chelating ligand, recently synthesized and claimed to be able to bind to Cu(II) ions forming stable complexes while leaving unaltered the level of essential metal ions, was scrutinized using a combined theoretical and experimental approach. A multistep synthetic procedure was used to synthesize the ligand, whose chelating properties along with the stability of the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Copper is an essential metal ion for biological functions already present in the human body, whose imbalance can, however, become severely detrimental inducing cellular damage and resulting to be more toxic than the Fe­(III) ion. In fact, it has been found that Cu­(II) plays a role in the pathogenesis of several neurological disorders . The studied ligand, II , may decrease Cu toxic effects acting as a chelator and, therefore, removing copper excess from biological environments.…”
Section: Resultsmentioning
confidence: 99%
“…Copper is an essential metal ion for biological functions already present in the human body, whose imbalance can, however, become severely detrimental inducing cellular damage and resulting to be more toxic than the Fe­(III) ion. In fact, it has been found that Cu­(II) plays a role in the pathogenesis of several neurological disorders . The studied ligand, II , may decrease Cu toxic effects acting as a chelator and, therefore, removing copper excess from biological environments.…”
Section: Resultsmentioning
confidence: 99%
“…A major section of pharmaceutical applications of L1 involves many categories of patients affected by metal intoxication in addition to iron [256,257]. These include the toxicity and modulation of essential metals, such as copper and zinc, and the toxicity of xenobiotic metals, such as aluminium, indium, gallium, uranium, americium, and plutonium, most of which are in competition with iron (Table 2) [48,111,[258][259][260][261]. The prospects of orally administered clinical applications of L1 in the detoxification of many of these xenobiotic metals, which are widely and routinely used, include radiolabelled gallium in clinical diagnostic procedures, and also uranium and plutonium used in warfare ammunition and in the nuclear industry, respectively [48,111].…”
Section: Clinical Effects Of Deferiprone In Non-iron-loaded Patient C...mentioning
confidence: 99%